The Japanese mind : - Christopher, Robert C.
Somewhat a bit dated, yet a this book is considered to be a classic. The author brings three decades of travel, research and understanding of this ancient tribe. An entertaining and thorough introduction to all things Japanese. Much has been written about Japanese management. But this is the first book to explain the people, the life, and the culture of that fascinating nation.